JinQi Jiangtang Tablet Regulates Gut Microbiota and Improve Insulin Sensitivity in Type 2 Diabetes Mice - Ying Cao; Guowang Yao; Yuanyuan Sheng; Li Yang; Zixuan Wang; Zhen Yang; Pengwei Zhuang; Yanjun Zhang (Journal of Diabetes Research)
Background. Gut microbiota modulates the barrier function and host inflammatory state in metabolic disease. JinQi Jiangtang (JQJT) tablets are a traditional Chinese medicine for the treatment of diabetes. However, the low bioavailability of its chemical compositions makes it hard to explain the pharmacological mechanisms. Method. Diabetic mice were orally treated with JQJT tablets for 5 weeks. Fasting blood glucose and the level of HbA1c were measured, and ITT were conducted to determine the insulin improvement effect of JQJT tablets. The regulation effect on gut microbiota was assessed by 16S rRNA gene sequencing on an Illumina HiSeq platform. The concentration of short-chain fatty acids was measured by HS-GC/MS. D-LA leakage experiment and PAS staining were used to check the function of the gut barrier. The levels of the inflammatory cytokines were determined by using an ELISA kit. Results. This study showed that JQJT tablets downregulated fasting blood glucose and HbA1c and regulated gut microbiota. JQJT tablet-treated groups exhibited a more sensitive reaction after a small-dose injection of short-acting insulin. T2DM mice treated with JQJT tablets showed a higher abundance of Akkermansia spp. and lower abundance of Desulfovibrio. JQJT tablets increased the concentration of acetic acid, propionic acid, and butyric acid; in particular, butyric acid was significantly increased with respect to the MOD group. Gut mucosal barrier function experiment showed that the level of D-LA was obviously decreased in JQJT tablet-treated groups compared with the model group and the number of goblet cells was significantly increased by JQJT tablet treatment. JQJT tablets could also reduce the levels of TNF-α, IL-6, and MCP-1, which were related to insulin resistance. Conclusion. We demonstrated that JQJT tablets could improve T2DM insulin resistance, regulating the gut microbiota and promoting the production of SCFAs. The mechanism was related to increasing the gut barrier function and reducing the host inflammatory reaction.